And they just keep coming: four new genera of dark sac spiders from southern Africa (Araneae, Trachelidae) - Charles R. Haddad (African Invertebrates)
As part of ongoing revisions of the Afrotropical Trachelidae, four new genera are described from southern Africa: Foordana gen. nov., with F. distincta sp. nov. from South Africa (Eastern Cape, Free State, KwaZulu-Natal and Western Cape) as the type species, F. flavipoda sp. nov. from the Free State, F. kasouga sp. nov. from the Eastern Cape and KwaZulu-Natal, and a fourth undescribed species from Zimbabwe; the monotypic Mushimane gen. nov., with M. tswibilinki sp. nov. from KwaZulu-Natal as the type species; Namaquella gen. nov., with N. arida sp. nov. from the Northern Cape as the type species and N. samanthae sp. nov. from the Western Cape; and Rukuluk gen. nov. from South Africa, with R. gramineus sp. nov. from the Northern Cape as the type species and a second undescribed species from KwaZulu-Natal known only from juveniles.